Japan's new spatial development strategy: challenges of the 21st century - I. L. Timonina (Японские исследования, 2020)
The socio-economic consequences of regional unevenness remain one of the major problems of Japan's development in the 21st century. Despite some success in regional economic policy, the main quantitative indicators of territorial-economic proportions/imbalances have changed little over the past 30 years. However, a number of internal and external factors have made it necessary to adjust approaches to regional strategic planning. These include globalization and the changing positioning of Japan in the world market, the partial loss of competitive positions in Asian markets, and increased competition between “international” cities for foreign investment. Internal factors include the decline of the Japanese population at a rate higher than previously expected, changes in people's lifestyles and shifts in their value system, the increasing importance of such of its components as stability, security, favorable environmental conditions, attractive landscapes, and diversification of lifestyles. The new national spatial strategy of the 21st century is based on the idea of creating a multi-layered “compact and networked territorial structure”, which should ensure the availability of social services for residents of all localities by optimizing the social infrastructure and forming “new urban cores”. The economic development of regions should focus on the development of industries that rely on local resources and take into account local specifics, as well as the creation of “ecosystems” of innovations. Along with reviving the regional and rural economy, Japan's new spatial strategy also aims to adjust the concentration of population and economic potential of large megacities (primarily Tokyo) and at the same time strengthen their global competitiveness. As necessary conditions for achieving ambitious goals, the Spatial Strategy calls for achieving economic growth, increasing industrial productivity, building innovation through regional resources and interregional cooperation, increasing the participation of women and older people in work and public life, using modern “smart” technologies and sharing economy formats. The traditional imperative in formulating Japan's spatial development strategy remains the obvious desire to solve the problems of territorial unevenness in conjunction with solving other socio-economic problems of the country, in particular the problems of ecology and demographic decline (which is especially noticeable in the regions), issues of improving production and social infrastructure.